Analisis Tantangan Guru Dalam Implementasi Pembelajaran Kelas Rangkap (PKR) Di Sekolah Dasar - Kurniawati, Agnes Fibriana; Andita, Cahyo Dwi (UNIVED Press, Universitas Dehasen Bengkulu, 2025)
This study examines the effectiveness of Multigrade Learning (PKR) at SDN 2 Sumber Harta, focusing on planning readiness, teaching method variation, classroom management, and learning evaluation. It addresses a research gap concerning the implementation of PKR in elementary schools with 221 class models in remote areas, which has been scarcely studied. The study aims to understand teachers’ challenges and strategies in conducting PKR to improve learning quality. A descriptive qualitative method was employed, using interviews, observations, and documentation for data collection. Findings reveal that teachers face limitations in preparing lesson plans and teaching modules, limited variation in teaching methods, and ineffective classroom management. Learning evaluations rely mainly on simple written tests and limited use of student worksheets. Theoretical implications reinforce multigrade learning concepts emphasizing thorough planning and adaptive classroom management, while practical implications highlight the need for teacher training and improved facilities. The study concludes that enhancing teacher capacity and providing adequate learning media are crucial for successful PKR implementation. It recommends increased training and resource support to improve multigrade learning quality in remote areas.